Clinical Features of 50 Patients With Primary Adrenal Lymphoma - Wang, Yan; Ren, Yan; Ma, Lifen; Li, Jian; Zhu, Yuchun; Zhao, Lianling; Tian, Haoming; Chen, Tao (Frontiers in Endocrinology, 2020)
Background and Objective: Primary adrenal lymphoma is a rare, progressive, easily misdiagnosed adrenal tumor with a poor prognosis. There are limited data on its clinical characteristics, and these have been derived from small sample studies. This study aimed to identify the clinical characteristics and prognosis of primary adrenal lymphoma. Methods: This single-center study retrospectively analyzed data of 50 primary adrenal lymphoma patients treated between January 2008 and January 2018. Demographic information, biochemical indexes, computed tomography images, pathological findings, treatment regimens, and prognostic factors were analyzed. Results: The median age of onset was 60.3 years, and 30 (60.0%) of 50 patients were male. Abdominal pain was the most common symptom, followed by incidentaloma and B symptoms. On average, patients presented with elevated lactate dehydrogenase (348 IU/L, normal range 110–220 IU/L) and hydroxybutyrate dehydrogenase levels (287 IU/L, normal range 72–182 IU/L) and decreased high-density lipoprotein cholesterol levels (0.88 mmol/L, normal range > 0.9 mmol/L). Bilateral lesions in the adrenal glands were observed in 30 (60.0%) patients. Computed tomography showed that 42 (84%) patients had signs of infiltration. Diffuse large B-cell lymphoma was present in 44 (88%) patients. Immunohistochemistry revealed that 70.6% (12/17), 89.5% (17/19), 92.0% (23/25), and 68.8% (11/16) of patients were positive for MYC, p53, BCL2, and both MYC and BCL2, respectively. Combined chemotherapy was associated with a good prognosis. Conclusions: Early diagnosis of primary adrenal lymphoma depends on a combination of biochemical examination, imaging studies, and pathological biopsy, and combined chemotherapy may lead to a better prognosis.